Cegah dan Turunkan Hipertensi Melalui Senam Refleksi Tepuk Nadi Pada Kelompok Lansia Di Kota Banjar - Aneng Yuningsih; Feni Nurwahyu Ningrat; Agisti Raudhatul Fitri (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2024)
Introduction: Hypertension, often known as the 'silent killer', has become one of the biggest health problems among the elderly throughout the world. Considering the serious impact it can have on health, understanding the prevention and management of hypertension in the elderly is very important. Objective: to increase knowledge of Preventing and Reducing Hypertension Through Pulse Clapping Reflexology Exercises in Elderly Groups. This activity was attended by a group of 132 active elderly people. Method: Implementation of community service is carried out through stages: Preparation, Socialization, Implementation of Activities (Explanation of material, Simulation and Evaluation) and Closing. Results: Based on the data above, it can be seen that the problems experienced by activity participants are: Furthermore, the evaluation results at the end of the activity showed an increase in understanding of the material presented by the presenters. With an average increase of 63%. This community service activity is documented in the image below. Conclusion: Based on the results of the evaluation of community service activities, Preventing and Reducing Hypertension Through Pulse Clapping Reflexology Exercises in Elderly Groups in Banjar City through education and simulation has experienced quite a significant increase.